Investigation on Hadiths in al-Bayân al-Mulamma’ ‘an Alfâẕ al-Lam’ Written by Sahal Mahfudz | الاطلاع على أحاديث ((البيان الملمع عن ألفاظ اللمع)) للشيخ محمد أحمد سهل بن محفوظ الحاجيني - Ulin Nuha (Al-Zahra: Journal for Islamic and Arabic Studies)
The book of al-Bayân al-Mulamma’ ‘an Alfâẕ al-Lam’ written by Sahal Mahfudz, one of the Nusantara’s Ulama, is the comments of the Imam Syairozi’s book, al-Lam’ fî Uṣûl al-Fiqh. In Sahal’s book, there is a number of hadith without mentioning conductors of takhrij (hadith extraction and authentication in the collections). Based on this, the activity of takhrij is an important matter.